Pearls and Pitfalls in the Diagnosis of Adult Celiac Disease - Hugh J Freeman (Canadian Journal of Gastroenterology)
In adults with diarrhea or suspected malabsorption, a diagnosis of celiac disease requires that two criteria be fulfilled: first, a demonstration of typical pathological changes of untreated disease in biopsies from the proximal small bowel; and second, evidence should exist that clinical (and/or pathological) changes are gluten-dependent, most often as an unequivocal response to a gluten-free diet. Pathological abnormalities of celiac disease may include severe (‘flat’) or variably severe (mild or moderate) small bowel mucosal architectural abnormalities that are associated with both epithelial cell and lymphoid cell changes, including intraepithelial lymphocytosis. Architectural changes tend to be most severe in the duodenum and proximal jejunum and less severe, or absent, in the ileum. These findings, while characteristic of celiac disease, are not specific because several other conditions can produce similar changes. Some serological assays (eg, tissue transglutaminase antibody assays) are very useful screening tools in clinical practice because of their high specificity and sensitivity, but these do not provide a definitive diagnosis. The most critical step in the diagnosis of celiac disease is the demonstration of its gluten-dependent nature. The clinical response to gluten restriction in celiac disease is usually reflected in the resolution of diarrhea and weight gain. Normalization of biopsy changes can be first shown in the most distal intestinal sites of involvement, and later, sometimes only after prolonged periods (months to years) in the duodenum. Rarely, recurrent (or refractory) celiac disease may occur after an initial gluten-free diet response. Finally, some with ‘sprue-like intestinal disease’ cannot be classified because a diet response fails to occur. This may be a heterogeneous group, although some are eventually found to have a malignant lymphoma.